PEFEKTIVITAS TEKNIK HORIZONTAL DALAM MENINGKATKAN OPERASI HITUNG PERKALIAN BAGI ANAK BERKESULITAN BELAJAR - Desmawira, Ganda Sumekar, Rahmatrisilvia (Jurnal Penelitian Pendidikan Khusus, 2013)
The background this research was, there is a child who can not do ing multiplication to acount  at SD N 29  Dadok Tunggul Hitam Padang. horizontal techniques is  manner a child for done multiplication, the purpose of this accont skill for dyscalculia child at 29 Dadok Tunggul Hitam Padang. Type of study is a Single Subject Researh with A-B-A desaign. The result of this study is horizontal techniques effective to go up of multiplication to account for a dyscalculia child at 29 N Dadok Tunggul Hitam Padang.\